Training Arabic Language Teachers in Pronunciation through the Natural Method across Educational Levels in Indonesia: تدريب مدرسي اللغة العربية على نطق الأصوات بالأسلوب الطبيعي في جميع المراحل التعليمية بإندونيسيا - Ridha Darmawaty; M. Kamil Ramma Oensyar; Ali Ma’youf al-ma’youf (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2025)
Teachers and learners of Arabic across various levels of education frequently encounter difficulties that impede the development of their linguistic competence. A principal challenge lies in the articulation of Arabic phonemes absent from their mother tongue, particularly for Indonesian speakers. This circumstance gives rise to phonological interference, namely the tendency to substitute unfamiliar sounds with those from their first language. To address this issue, the present study proposes the utilisation of Uslub al-Tabi’iyyah wa al- Muḥākāt (the method of natural imitation), which relies on spontaneous, unplanned articulatory patterns as the foundation for training in the pronunciation of unfamiliar phonemes. The researchers implemented an intensive training programme employing a direct procedural approach, encompassing the stages of analysis, design, implementation, evaluation, and reflection. The findings reveal that this method was positively received by both teachers and learners, as it was perceived as straightforward and consonant with  their natural learning tendencies. However, learners continued to experience difficulties in pronouncingcertain consonants such as ṣād (ص), ḍād (ض), ṭāʾ (ط), and ẓāʾ (ظ) especially within words and sentences. These challenges were shaped by previous linguistic habits and constrained training time. Overall, the method of natural imitation has proven to be more practical, effective, and aligned with learners’ linguistic instincts, rendering it a viable primary option in pronunciation instruction, particularly at the introductory level.